Children's Executive Function Attenuate the Link Between Maternal Intrusiveness and Internalizing Behaviors at School Entry. (21st December 2018) - Gueron-Sela, Noa; Bedford, Rachael; Wagner, Nicholas J.; Propper, Cathi B.
Abstract : The goal of this study was to examine the independent and interactive roles of harsh-intrusive maternal behaviors and children's executive function in the development of internalizing behaviors across the first years of school. A diverse sample (58% African American, 42% European American) of 137 children (48% female) was followed from kindergarten (age 5 years) through school entry (ages 6–7 years). At age 5, maternal harsh-intrusive parenting behaviors were rated from a mother–child structured play task, and children completed 3 executive function tasks that measured inhibitory control, working memory, and attention set-shifting. Teachers reported on children's internalizing behaviors at ages 5, 6, and 7. Harsh-intrusive parenting behaviors at age 5 years were positively related to internalizing behaviors in the first years of school, whereas high executive function abilities at age 5 years were related to lower internalizing behaviors in the first years of school. In addition, executive function buffered the association between parenting behaviors and internalizing behaviors such that the link between harsh-intrusive parenting and child internalizing behaviors was evident only among children with low executive function and not among children with high executive function. Interventions that focus on reducing negative parenting behaviors and improving children's executive function may prevent internalizing behaviors from increasing during times of social and academic challenge.